DEVELOPMENT OF DIGITAL FLIPBOOK TEACHING MATERIALS AT THE PALACE OF HINGGAP SENAPELAN ON THE MATERIAL OF THE INDONESIAN NATIONAL MOVEMENT FOR GRADE XI OF STATE SENIOR HIGH SCHOOL 1 PEKANBARU: Pengembangan Bahan Ajar Flipbook Digital Pada Istana Hinggap Senapelan Materi Pergerakkan Kebangsaan Indonesia Kelas XI SMA Negeri 1 Pekanbaru - Karina Putri Hazelvy; Suroyo; Ahmal (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This study aims to develop, evaluate the feasibility, and implement Flipbook-based digital teaching materials related to the Indonesian National Movement at the Perhentian Senapelan Palace for eleventh-grade students at SMA Negeri 1 Pekanbaru. This study addresses issues identified during the analysis phase, including the development, feasibility, and implementation of digital Flipbook teaching materials. The ADDIE (Analysis, Design, Development, Implementation, and Evaluation) development model was used. The development of digital Flipbook teaching materials was designed through material selection, storyboard design, and instrument development. The validation process concluded with validation by material experts and media experts. The validation by material experts yielded a score of 85% (very feasible), while the validation by media experts yielded a score of 88% (very feasible), indicating that the digital Flipbook teaching materials met the quality standards required for classroom implementation. Field trials were conducted in two stages: a small group of ten students and a large group of thirty students. Student responses demonstrated high feasibility, with scores of 89% in the small group and 87% in the large group. In the feasibility test, the Flipbook-based digital teaching materials at the Perhentian Palace in Senapelan obtained a percentage of 89% in the